2007
DOI: 10.1038/sj.bmt.1705692
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of low-dose interleukin-2 vs cyclosporine A and interferon-γ after high-dose chemotherapy with peripheral blood progenitor support in women with high-risk primary breast cancer

Abstract: High-risk primary breast cancer patients treated with high-dose chemotherapy (HDC) and stem cell support (SCS) have shown prolonged disease-free survival (DFS) in many studies; however, only one trial has demonstrated an overall survival benefit (OS). We hypothesize that the period following myeloablative therapy is ideal for immunologic manipulation and studied the effects of two different methods of immunotherapy following HDC with SCS aimed at the window of immune reconstitution. Seventy-two women with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…At a median follow up of 67 months, no significant difference was observed in disease free survival (DFS) or overall survival (OS) between the two treatment groups. Furthermore, when compared with the high dose arm without any immune manipulation, the results were very similar [74]. Subcutaneous IL-2 and IFN were consecutively [75] or simultaneously [76] given at low dose in another pilot study and in one phase II non-randomised trial 36 or 40 advanced breast cancer patients with failure of previous conventional treatments were included.…”
Section: Interferons Plus Interleukin-2mentioning
confidence: 91%
“…At a median follow up of 67 months, no significant difference was observed in disease free survival (DFS) or overall survival (OS) between the two treatment groups. Furthermore, when compared with the high dose arm without any immune manipulation, the results were very similar [74]. Subcutaneous IL-2 and IFN were consecutively [75] or simultaneously [76] given at low dose in another pilot study and in one phase II non-randomised trial 36 or 40 advanced breast cancer patients with failure of previous conventional treatments were included.…”
Section: Interferons Plus Interleukin-2mentioning
confidence: 91%
“…Interferon-gamma was used in clinical trials for melanoma but no significant improvement for patients was observed ( 261 264 ). In fact, IFN-γ treatment had no contribution to the outcomes of patients with metastatic renal cell carcinomas ( 265 ), leukemia ( 266 ), pancreatic carcinoma ( 267 ), breast cancer ( 268 ), or into the postoperative surgical therapy for colon cancer ( 269 ). Furthermore, a phase 3 trial of IFN-γ plus standard treatment with carboplatin/paclitaxel versus carboplatin or paclitaxel alone, for treated advanced ovarian tumors, was early terminated due to a higher incidence of serious hematological toxicities in patients receiving combined therapy compared with chemotherapy alone ( 270 ).…”
Section: Ifn-γ In Cancermentioning
confidence: 99%
“…However, the normZ scores of IL2 and IL2R were close to zero in the CTL and TNBC CRISPR screens, respectively. Interestingly, we found that interleukin-2 failed to demonstrate its efficacy in breast cancer patients during a phase III clinical trial (48). Similarly, pegylated recombinant interleukin-10 or pegilodecakin had low efficacy against pancreatic ductal adenocarcinoma during a phase III clinical trial (49).…”
Section: Resultsmentioning
confidence: 99%